Employers’ recruitment contexts and hiring preferences in the German youth labor market - Protsch, Paula [Verfasser] (My University, 2021)
„This article examines whether and to what extent employers’ hiring preferences regarding male and female applicants’ cognitive and noncognitive skills signals vary with the regional and occupational recruitment context. According to the job-competition model, supply and demand might increase or decrease young people’s opportunities over and above the effect of inequalities linked to individuals’ ascribed characteristics and education. Few studies have considered the interrelatedness of regional and occupation-specific supply and demand and how this affects employers’ hiring preferences in youth labor markets. I analyze a factorial survey experiment conducted on the German apprenticeship market, which was integrated into a larger representative employer survey. Employers evaluated a randomly assigned set of résumés and indicated how likely it was that each applicant would be invited to a job interview or employment test. Statistics on regional and occupational supply and demand and the occupational gender composition were matched to the employers. The results indicated that employers favored applicants with better skills signals and preferred male applicants in male-dominated occupations. Further, employers who encountered or anticipated recruitment difficulties in their region and occupation rated applicants with the same skills signals more positively than employers in contexts with applicant oversupply. However, female applicants did not receive significantly higher ratings in male-dominated occupations in contexts with excess employer demand, nor did the gender gap in ratings decrease considerably.“ (author‘s abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; G 1.2 Arbeitsmarkt; 370; Betrieb; Arbeitgeber; Stellenbesetzung; Personalauswahl; Arbeitsplatzangebot; Jugendlicher; Regionale Faktoren; Regionaler Arbeitsmarkt; Ausbildungsstellenmarkt; Geschlechtsspezifische Faktoren; Qualifikationsprofil